PEMBERATAN PIDANA OLEH MAHKAMAH AGUNG DALAM PERKARA ANAK DITINJAU BERDASARKAN PRINSIP JUDEX JURIS (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 526K/PID.SUS/2019) - Virlieni Erika Putri; R Rahaditya (Jurnal Hukum Adigama, 2020)
Judge's judgment is essential in implementing the regulation on children. The principle of Supreme Court precedents made the court judge not authorized to file criminal proceedings against children. A child who commits a criminal act will continue to carry out a judicial process whose judicial process is different from the court process in general. However, in child criminal cases in the decision number: 526K/Pid.Sus/2019 the Supreme Court judge imposes a criminal weight against the offender's child. Meanwhile, the Child Protection Law defines the best principle for children. The research method used is normative juridical research. The results showed, first juridically, the principles of the Supreme Court as judex juris make Supreme Court judges not authorized to enforce criminal sanctions. The severity of a sanction is also not the object of examination in the cassation stage. Second, during the examination considerations presented by a Supreme Court judge are considered to reduce any resistance to children. So judges are considered not paying attention to the fairness of both sides.